2011
DOI: 10.1063/1.3528724
|View full text |Cite
|
Sign up to set email alerts
|

Structural and dynamical properties of solid ammonia borane under high pressure

Abstract: The structural and dynamical properties of solid ammonia borane were investigated by means of extensive density functional theory calculation up to 60 GPa. Molecular dynamics simulations suggest that the Cmc2(1) phase found by recent room-temperature x-ray diffraction experiments can be obtained from the Pmn2(1) structure at high pressure and low temperature. Two new high-pressure phases were found on further compression at room temperature. We also found that all three high-pressure phases have proton-ordered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 47 publications
4
43
0
Order By: Relevance
“…The more recent XRD and DFT study by Lin et al [64] in 2012 indicated that the structure of phase IV might actually take a monoclinic structure with the space group of P2 1 and 4 molecules in the unit cell. But this monoclinic structure is different from those predicted by Wang et al [67] although they all take the P2 1 space group. All these studies indicated that phase IV to IV 0 is an iso-structural transition.…”
Section: Phase IV and Ivmentioning
confidence: 57%
See 4 more Smart Citations
“…The more recent XRD and DFT study by Lin et al [64] in 2012 indicated that the structure of phase IV might actually take a monoclinic structure with the space group of P2 1 and 4 molecules in the unit cell. But this monoclinic structure is different from those predicted by Wang et al [67] although they all take the P2 1 space group. All these studies indicated that phase IV to IV 0 is an iso-structural transition.…”
Section: Phase IV and Ivmentioning
confidence: 57%
“…Transitions of phase III to III 0 , IV to IV 0 are indentified as iso-structural [62,63]. The transition from phase IV to VI was observed by Raman spectroscopy study [70] and predicted to be first-order transformation by theoretical study [67]. The boundaries for decomposition and high-temperature phase V were based on Nylén et al's [56,65] Raman spectroscopy and XRD studies; the I-III boundary above room temperature was from Sun et al's [69] Raman spectroscopy study; I-II and I-III boundaries below room temperature were from Andersson et al [59] and Najiba et al [75].…”
Section: P-t Phase Diagrammentioning
confidence: 93%
See 3 more Smart Citations